20,000 leagues under the sea - Nordlicht, Lillian; Butz, Steve; Verne, Jules, 1828-1905. (Milwaukee : Raintree, 1980)
An adaptation of the 19th-century science fiction tale of an electric submarine, its eccentric captain, and undersea world which anticipated many of the scientific achievements of the 20th century.
5.5
5-8
5-8
Wilson's Children
Wilson's Junior High School
Keywords: Sea stories; Submarines -- Fiction; Science fiction; Sea stories; Submarines -- Fiction; Science fiction